Modern Biotechnology for Agricultural Development in Colombia (2018)
Colombia is currently one of the most promising countries with regard to its potential for agricultural development and for generating food supply for current and future human generations. This is owing to factors such as availability of land, water, topographical diversity, as well as political factors. Nevertheless, Colombia will reach this full potential if it adopts available technologies that can meet the current global challenges faced by the agriculture in the 21st century: among others, world population growth, increase in average life expectancy, high degree of malnutrition, climate change, wrong agricultural practices. Here is presented how modern biotechnology is an important ally as a wide range of technologies and innovative systems can be applied where they are most needed: for increasing cultivation productivity, resisting both biotic and abiotic factors, and ensuring food safety. In this study is showed evidence with regard to significant benefits of adopting biotechnological crops to contribute to food safety and how they are already being implemented in both developed and developing countries. Using modern technology, there are open opportunities for the country in search of circular bio-based economy, strengthen its food sovereignty and to serve as an agricultural breadbasket to Latin America and the World.